2003
DOI: 10.4141/p02-037
|View full text |Cite
|
Sign up to set email alerts
|

Sowing date affects yield components of canarygrass seed

Abstract: Canarygrass (Phalaris canariensis L.) crops are sown from June to mid-September in the southeastern area of the province of Buenos Aires, Argentina. Sowing dates in this range result in different growing temperatures and photoperiods that affect the duration of developmental stages, biomass production, and seed yield and its components. For Argentina, there are no reported studies that address these effects. This study on the effects of sowing date was conducted during four growing seasons (1996–1999) at the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 9 publications
3
2
1
Order By: Relevance
“…This lack of a seeding date effect on kernel weight was also reported in other studies (Miller 2000;Bodega et al 2003). The intercept was 7.2 g 1000 kernels…”
Section: Seeding Datesupporting
confidence: 88%
See 2 more Smart Citations
“…This lack of a seeding date effect on kernel weight was also reported in other studies (Miller 2000;Bodega et al 2003). The intercept was 7.2 g 1000 kernels…”
Section: Seeding Datesupporting
confidence: 88%
“…This trend was observed by Miller (2000) in Saskatchewan but not by Bodega et al (2003) in Argentina.…”
Section: Seeding Datementioning
confidence: 69%
See 1 more Smart Citation
“…2), in agreement with Bodega et al (2002Bodega et al ( , 2003 for this species and Peltonen-Sainio et al (2007) for wheat, barley, oats and rice. One of the few exceptions to this general relationship was, as mentioned above, the promising Moroccan population 42, the high yield of which was due to its high grain weight; this was also the case for the Dutch cultivar Cantate (accession 60).…”
Section: Correlations Between Characterssupporting
confidence: 90%
“…In the current work and in spite of previous reports that the genetic variation observed in canaryseed is low (Poverene et al 1994;Bodega et al 1995Bodega et al , 2003Putnam et al 1996;Miravalles et al 2002;Matus-Cadiz andHucl 1999, 2002), significant differences were found between the accessions for all evaluated characters (grain yield and its components, plant height and phenology) as described in the following sections (Table 2), although the combined analyses of variance over trials also demonstrated the presence of significant genotype (accession) )environment (trial) interaction (P 50.05).…”
Section: Results and Discusioncontrasting
confidence: 68%